Reduction of changeover time and solvent cleaning cost in tank cleaning process in paint manufacturing industry in Indonesia - Krisna Budi Juliantoro; Hibarkah Kurnia; Syarah Rizkia Feriaty (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
In the era of globalization, competition in the manufacturing industry is increasing, especially regarding product quality and customer service. One of the paint manufacturing companies in Indonesia has experienced an increase in production volume in line with increasing market demand, as reflected in annual sales growth of 25-29%. As a market leader in the field of marine coatings and protective coatings with a market share of more than 29%. These challenges impact the tank cleaning process, which directly affects the duration of change over time with each product changeover. Based on company standards, the ideal changeover time is 30 minutes for each product changeover during tank cleaning. This research aims to reduce the duration of changes over time and reduce wasted costs in purchasing cleaning solvents (solvents) needed in the tank cleaning process at each batch change. The method of this research is a combination of A3 Problem Solving and Single-Minute Exchange of Dies (SMED), which is designed to compile documentation solutions in a consistent, clear, and structured manner. Research findings reveal that the duration of the initial change required reaches 95 minutes with a monthly solvent purchase cost of IDR 10,500,000. By converting several internal activities into external activities, the duration of the change to be completed was reduced to 30 minutes, and the completion cost was IDR 3,500,000 per month. Overall, this research shows an over-time change efficiency of 68% and operational cost savings of up to 66% in the tank cleaning process.